A Protein-Centric View of in Vitro Biological Model Systems for Schizophrenia. (30th August 2021) - Chandrasekaran, Abinaya; Jensen, Pia; Mohamed, Fadumo A.; Lancaster, Madeline; Benros, Michael E.; Larsen, Martin R.; Freude, Kristine K.
Abstract: Schizophrenia (SCZ) is a severe brain disorder, characterized by psychotic, negative, and cognitive symptoms, affecting 1% of the population worldwide. The precise etiology of SCZ is still unknown; however, SCZ has a high heritability and is associated with genetic, environmental, and social risk factors. Even though the genetic contribution is indisputable, the discrepancies between transcriptomics and proteomics in brain tissues are consistently challenging the field to decipher the disease pathology. Here we provide an overview of the state of the art of neuronal two-dimensional and three-dimensional model systems that can be combined with proteomics analyses to decipher specific brain pathology and detection of alternative entry points for drug development. : Schematic diagram of stem-cell derived two-dimensional schizophrenia (SCZ) culture models (left column) vs three-dimensional (3D) SCZ brain organoid models (middle column) to engineer neural networks for translational medicine. SCZ patient cells are reprogrammed toward human induced pluripotent stem cells (hiPSC). Derived 3D brain organoids from hiPSCs serve as a model for further investigations. The application of proteomics and posttranslational modification specific proteomics (PTMomics) on 3D organoids could contribute to a wealth of information regarding the underlying mechanisms of the diseases and cell responses to in vivo settings (right column).